2021
DOI: 10.3390/insects12121078
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide Resistance Monitoring in Field Populations of the Whitebacked Planthopper Sogatella furcifera (Horvath) in China, 2019–2020

Abstract: Monitoring is an important component of insecticide resistance management. In this study, resistance monitoring was conducted on 18 field populations in China. The results showed that S. furcifera developed high levels of resistance to chlorpyrifos and buprofezin, and S. furcifera showed low to moderate levels of resistance to imidacloprid, thiamethoxam, dinotefuran, clothianidin, sulfoxaflor, isoprocarb and ethofenprox. Sogatella furcifera remained susceptible or low levels of resistance to nitenpyram. LC50 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The large-scale and irrational use of chemical pesticides against pests has led to various problems such as environmental contamination, food security, phytotoxicity, disruption of non-target organisms, pest resurgence and insecticide resistance [ 1 , 13 , 14 ]. Previous studies have shown that the field populations of WBPHs have developed high levels of resistance to 15 compounds worldwide [ 15 ]; the rapid increase of pesticide resistance in WBPH populations has led to an emphasis on the development of environmentally friendly management methods.…”
Section: Introductionmentioning
confidence: 99%
“…The large-scale and irrational use of chemical pesticides against pests has led to various problems such as environmental contamination, food security, phytotoxicity, disruption of non-target organisms, pest resurgence and insecticide resistance [ 1 , 13 , 14 ]. Previous studies have shown that the field populations of WBPHs have developed high levels of resistance to 15 compounds worldwide [ 15 ]; the rapid increase of pesticide resistance in WBPH populations has led to an emphasis on the development of environmentally friendly management methods.…”
Section: Introductionmentioning
confidence: 99%
“…The variation of insecticide resistance in populations of diamondback moth Plutella xylostella (Linnaeus), a cruciferous pest inhabiting different geographical regions of the world, to OPCs, pyrethroids, and biopesticides have been described [14,15]. High resistance levels to OPCs and growth regulators and the formation of tolerance to neonicotinoids have been detected between 2019 and 2020 in China in populations of the white-backed planthopper, the rice pest, Sogatella furcifera [16]. Van den Berg et al (2022) illustrated the potential for insecticide resistance development in African countries' cotton, corn, vigna, and tomato pests [17].…”
Section: Introductionmentioning
confidence: 99%
“…In the modern world, the protection of plants, animals, and humans against arthropod pests, ectoparasites, and vectors of vector-borne diseases is carried out mainly through the use of pesticides [1][2][3][4]. In response to insecticidal action, insects are capable of developing tolerance or resistance to insecticides [2,4]. For example, more than 600 species of insects and mites are known to be resistant to at least one insecticide in their populations [5].…”
Section: Introductionmentioning
confidence: 99%